Selective extraction, separation and recovery of Cu(II) in presence of Zn(II) and Ni(II) from leach liquor of waste printed circuit board using microcapsules coated with Cyanex 272 - Md. Sohrab, Hossain; Md. Fazlul, Bari, Dr.; Samsul Baharin, Jamaludin, Prof. Dr.; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Mohd. Omar, Ab. Kadir (Springer Verlag, 2013)
Link to publisher's homepage at link.springer.com/